Dampak Insentif Perpajakan dan Lingkungan Sosial terhadap Kepatuhan Pajak pada Masa Pandemi Covid-19 di Kota Padang - Popi Fauziati; Nailal Husna; Yetty Morelent (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2022)
The COVID-19 pandemic that hit Indonesia in early March 2021 brought significant changes to the national economy, including micro, small and medium enterprises. One of the policies carried out by the government to reduce the impact of the pandemic is by providing economic stimulus in the form of tax incentives for business actors. The social environment in the concept of taxation is that humans will see the surrounding environment which should understand taxation. Tax incentives and the social environment given to business actors will affect their tax compliance. This study aims to empirically examine the effect of tax incentives and the social environment on tax compliance. The population studied by SME in Padang City and the sampling method used in this study was purposive sampling. The samples obtained were 146 companies and the data collected were tested using multiple regression. The test results show that tax incentives and social environment have an effect on tax compliance.